2018
DOI: 10.1002/chem.201802625
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of a NHC‐Coordinated Trisilacyclopropylidene and Its Coordination Behavior

Abstract: With a co-reduction procedure using 2 equivalents Mes SiCl and 1 equivalent NHC →SiCl an NHC-adduct of a trisilacyclopropylidene (SiMes ) SiNHC 1 was synthesized. Addition of NHC to 1 results in quantitative carbene exchange under release of NHC to yield (SiMes ) SiNHC 2. Both NHC-coordinated trisilacyclopropylidenes coordinate to BH . In reaction of 1 with SiMe N a NHC-coordinated trisilane with an exocyclic Si=N double bond is formed. With diphenylacetylene 1 undergoes a ring expansion at room temperature to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…A similar 11 B NMR signal was reported for donor acceptor complexes with BH 3 such as the NHC-coordinated trisilacyclopropylidene borane complex BH 3 NHC Me4 Si 3 Mes 4 ( δ 11 B = −36.3 ppm in C 6 D 6 ). 45 The signal of Si1 in 5 was detected at −155.2 ppm. This shows that upon coordination of BH 3 to 3 the signal of Si1 is shifted by 100 ppm to lower field.…”
Section: Resultsmentioning
confidence: 99%
“…A similar 11 B NMR signal was reported for donor acceptor complexes with BH 3 such as the NHC-coordinated trisilacyclopropylidene borane complex BH 3 NHC Me4 Si 3 Mes 4 ( δ 11 B = −36.3 ppm in C 6 D 6 ). 45 The signal of Si1 in 5 was detected at −155.2 ppm. This shows that upon coordination of BH 3 to 3 the signal of Si1 is shifted by 100 ppm to lower field.…”
Section: Resultsmentioning
confidence: 99%
“…The first examples of acyclic bis­(silyl)­silylene NHC adducts IV were obtained by reductive debromination of the corresponding dibromosilanes with KC 8 in the presence of NHCs . Scheschkewitz et al and the Lips group reported cyclic derivatives V with a Si 3 scaffold via the reaction of NHC·SiBr 4 with a disilenyllithium reagent and the coreduction of NHC·SiCl 4 and Mes 2 SiCl 2 (Mes = 2,4,6-Me 3 -C 6 H 2 ), respectively . Very recently, Cowley and colleagues experimentally demonstrated the disilene–silylsilylene equilibrium for the first time by synthesizing and isolating NHC-stabilized bis­(silyl)­silylene VI from the corresponding donor-supported disilene .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, similar 11 B NMR signals (À 32.9 and À 36.3 ppm in C 6 D 6 ) were observed in borane complexes of NHC-coordinated trisilacyclopropylidenes. [27] Adduct formation with 2 using only a Lewis acid was achieved with AlBr 3 to yield 5 (Scheme 4). Upon coordination of AlBr 3 to 2 the transannular distance between Si1 and Si3 increases to 2.691 Å and the bond lengths between Si1À Si2 and Si2À Si3 are slightly elongated to 2.247(9) Å and 2.268(9) Å with respect to 2, but indicate still partial Si=Si double bond character in these bonds.…”
Section: Resultsmentioning
confidence: 99%